2013
DOI: 10.1042/bj20130609
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol kinase θ couples farnesoid X receptor-dependent bile acid signalling to Akt activation and glucose homoeostasis in hepatocytes

Abstract: DGKs (diacylglycerol kinases) catalyse the conversion of diacylglycerol into PA (phosphatidic acid), a positive modulator of mTOR (mammalian target of rapamycin). We have found that chenodeoxycholic acid and the synthetic FXR (farnesoid X receptor) ligand GW4064 induce the mRNA and protein expression of DGKθ in the HepG2 cell line and in primary human hepatocytes. Reporter gene studies using 1.5 kB of the DGKθ promoter fused to the luciferase gene revealed that bile acids increase DGKθ transcriptional activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 74 publications
2
12
0
Order By: Relevance
“…Therefore, our current results encourage us to identify and develop specifi c inhibitors/activators against every DGK isozyme that can be effective regulators and drugs against a wide variety of physiological events and diseases ( 4 ). For example, DGK ␣ : cancer cell growth ( 9,10,37,40 ), angiogenesis ( 41 ), T-cell proliferation ( 45 ), and T-cell anergy ( 12, 13 ); DGK ␤ : bipolar disorder ( 46, 47 ); DGK ␥ : actin reorganization ( 19 ), allergy ( 48 ), and insulin secretion ( 49 ); DGK ␦ : epidermal growth factor receptor signaling ( 50 ) and type 2 diabetes ( 51, 52 ); DGK : epidermal growth factor receptor signaling ( 53 ), lung cancer ( 54 ), bipolar disorder ( 55,56 ), unipolar depression ( 56 ), and attention-defi cit/hyperactivity disorder ( 56 ); DGK : hypospadias ( 57 ); DGK : seizure susceptibility/ long-term potentiation ( 58 ) and Huntington's disease ( 59 ); DGK : cell growth ( 60 ), T-cell receptor response ( 61 ), and brain ischemia ( 62 ); DGK : Ras signaling ( 63 ); and DGK : Parkinson's disease ( 64 ) and bile acid signaling ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our current results encourage us to identify and develop specifi c inhibitors/activators against every DGK isozyme that can be effective regulators and drugs against a wide variety of physiological events and diseases ( 4 ). For example, DGK ␣ : cancer cell growth ( 9,10,37,40 ), angiogenesis ( 41 ), T-cell proliferation ( 45 ), and T-cell anergy ( 12, 13 ); DGK ␤ : bipolar disorder ( 46, 47 ); DGK ␥ : actin reorganization ( 19 ), allergy ( 48 ), and insulin secretion ( 49 ); DGK ␦ : epidermal growth factor receptor signaling ( 50 ) and type 2 diabetes ( 51, 52 ); DGK : epidermal growth factor receptor signaling ( 53 ), lung cancer ( 54 ), bipolar disorder ( 55,56 ), unipolar depression ( 56 ), and attention-defi cit/hyperactivity disorder ( 56 ); DGK : hypospadias ( 57 ); DGK : seizure susceptibility/ long-term potentiation ( 58 ) and Huntington's disease ( 59 ); DGK : cell growth ( 60 ), T-cell receptor response ( 61 ), and brain ischemia ( 62 ); DGK : Ras signaling ( 63 ); and DGK : Parkinson's disease ( 64 ) and bile acid signaling ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gene Expression-Treatment of hepatocytes with CDCA stimulates Akt activity via mechanisms involving increased production of mitochondrial reactive oxygen species (32) and increased production of phosphatidic acid, a cellular metabolite that promotes Akt phosphorylation (33). These observations led us to investigate whether Akt plays a role in mediating the stimulatory effect of CDCA on FGF21 and ATF4 expression.…”
Section: Akt and Phosphorylated Eif2␣ Mediate The Stimulatory Effect mentioning
confidence: 99%
“…Renga et al found that the FXR-KLF11 (Kruppel-like factor 11) pathway plays an important role in regulating insulin secretion induced by blood glucose [29]. Cai et al found that FXR can inhibit the mRNA expression levels of phosphoenolpyruvate carboxykinase and glucose-6-phosphatase by increasing the expression of diacylglycerol kinase [30]. Transgenic mice fed high-fat Fig.…”
Section: Discussionmentioning
confidence: 99%